The EFL Students’ Pragmatic Competence Level in Pakistan - Ayman Riheel Alnaas Taha; Sajjad Hussain; Muhammad Sajid Aziz; Hafiz Ali Raza (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
Second language teaching and learning has been grounded greatly on pragmatics. It has been a very important aspect of L2 learners. Majority of the existing literature on this subject matter has paid much attention to diverse pedagogies in the teaching and learning of English and how to integrate pragmatics in the classroom teaching of the language. Experts in the teaching and learning of English as a second language have over the period proven that understanding the level of competence of students’ pragmatics in terms of Pakistan EFL learners is imperative for establishing curriculum in teaching pragmatic competence. This study therefore addresses this aspect and pushes the debate further for a deeper understanding. This research specifically seeks to examine the pragmatic competence level of Pakistan students L2 learners or speakers as well as the contribution of gender and the type of school regarding their competency level in pragmatic knowledge. As for institution type, the results show that there is a significant difference regarding implicate and speech acts. The situational routines do not prove any differences for school type.